Adaptation to climate change in cities of Mediterranean Europe - Pietrapertosa, Filomena (2023)
ABSTRACT: Cities across Mediterranean Europe face common climatic threats. They are highly vulnerable and very likely to suffer losses and damages due to heat waves, droughts, wildfires, landslides, and extreme coastal events. To this date, however, there is no systematic understanding of how cities in Mediterranean Europe are preparing to adapt to these impacts. To address this question, we analyse local adaptation plans in 73 cities located in 51 regions across 9 European countries along the Mediterranean Sea (France, Italy, Spain, Greece, Portugal, Croatia, Slovenia, Cyprus and Malta). We also investigate upper levels of planning to understand the influence of policy environments. Across the sample, 67 % of regions have adopted a plan, but only 30 % of the cities. The most common climate-related hazards these cities prepare for are extreme temperatures and rainfall, followed by drought and water scarcity, as well as floods and landslides. Without legal obligations, neither regional nor national adaptation policy frameworks seem to influence the development of urban plans. In some cases, cities are ahead of national policy. This paper sheds light on the progress of local adaptation planning in Mediterranean Europe and paves the way for further research in this climate-threatened geographical area.